Multifunctional Synthesis Approach of In:CuCrO2 Nanoparticles for Hole Transport Layer in High‐Performance Perovskite Solar Cells. (26th June 2019) - Yang, Boping; Ouyang, Dan; Huang, Zhanfeng; Ren, Xingang; Zhang, Hong; Choy, Wallace C. H.
Abstract: While there are very limited studies of doped ternary metal oxide based hole transport materials, a multifunctional synthesis approach of In doped CuCrO2 nanoparticles (NPs) as efficient hole transport layers (HTLs) including simplifying the synthesis requirements is proposed, enabling doping and achievement of treatment‐free HTLs. Remarkably, compared with conventional methods for synthesizing CuCrO2 NPs, the newly proposed azeotropic promoted approach dramatically reduces the reaction time by 90% and the calcination temperature by one‐third, which not only promotes high throughput production but also reduces power consumption and cost in synthesis. Equally important, indium is successfully doped into CuCrO2, which is fundamentally difficult in low temperature processes. The In doping offers less d–d transition of Cr 3+ and p‐type doping characteristics for improving HTL transmittance and conductivity, respectively. Interestingly, In doped CuCrO2 HTL with these improvements can be achieved by a simple ambient‐condition process and exhibits thermal stability up to 200 °C, which allows perovskite solar cells (PSCs) to achieve a power conversion efficiency of 20.54%. Meanwhile, the devices show good repeatability and photostability. Consequently, the work contributes to establishing a simple approach to realize pristine and doped multinary oxides based HTL for the development of practical and high performing PSCs. Abstract : A new azeotropic promoted approach is proposed to successfully synthesize In doped CuCrO2 under low temperatures in a short time. This In doped CuCrO2 HTL has thermal stability up to 200 °C, and exhibits improved optical transmission and carrier mobility, which is beneficial for achieving high performance perovskite solar cells.